(untitled) (Research, Society and Development, 2019)
The present article reports the influence of the annotations made by the nursing team in the medical records, passing through the hospital audit, in order to improve patient care. This is a bibliographical review, based on the collection of digital magazines, books, ordinances and government websites, bringing information about the concept of hospital audit, Auditor and a brief history on the implementation of these terms and professions in the health area. It is concluded that it is extremely important to raise awareness and motivation of nursing when filling in the progress sheets and medical records, trying to minimize communication or understanding failures about medical records, making it essential to perform the audit, correlating the correct annotations of the records to the quality of the nursing care.